Pengetahuan Remaja Putri tentang Menstruasi dengan Sikap Menghadapi Dismenore Kelas XI di SMA Muhammadiyah 7, Yogyakarta - Husnul Khotimah; Kirnantoro Kirnantoro; Fitnaningsih Endang Cahyawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Incidence of dysmenorrhea in the world is high. It was estimated about 50% women in the world suffer from dysmenorrhea in the menstrual cyclus. Incidence of primary dysmenorrhea in Indonesia was 54.89% and the rest of that were sufferers by secondary type. The Study which conducted in Jakarta find 83.5% college student had dysmenorrhea and 58.2% in Palembang. From the reported that dysmenorrhea caused 14% adolescent often did not go to school. The purpose of study was to know the relationship between knowledge of 11th grade adolescent girls about menstruation and attitudes toward dysmenorrhea at Muhammadiyah 7 Senior High School, Yogyakarta. This study used descriptive analytic methode with cross sectional approach. Study was conducted at Muhammadiyah 7 Senior High School, Yogyakarta on 10 September 2011. Samples was obtained by total sampling technique which consisted of 71 adolescent. The knowledge of 43 (60.6%) adolescent girls about menstruation at Muhammadiyah 7 Senior High School, Yogyakarta was good, and about 39 (54.9%) adolescent girls attitudes toward dysmenorrhea at Muhammadiyah 7 Senior High School, Yogyakarta on positive category. In conclusion, there was a significant relationship between knowledge of 11th grade adolescent girls about menstruation and attitudes toward dysmenorrhea at Muhammadiyah 7 Senior High School, Yogyakarta, evidenced by χ2 count>χ2 table (8.005>5.991) and p-value <0.05 (p=0.018< 0.05).